2015
DOI: 10.1016/j.coal.2015.03.013
|View full text |Cite
|
Sign up to set email alerts
|

Geochemistry and petrology of palaeocene coals from Spitzbergen — Part 2: Maturity variations and implications for local and regional burial models

Abstract: The version presented here may differ from the published version or from the version of record. If you wish to cite this item you are advised to consult the publisher's version. Please see the repository url above for details on accessing the published version and note that access may require a subscription.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
43
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(49 citation statements)
references
References 14 publications
4
43
0
Order By: Relevance
“…Throndsen (1982) estimated uplift of about 3.5 km in western central Spitsbergen. Marshall et al (2015) suggested that the base-Paleocene has experienced maximum burial temperatures of 120 °C in the central part of the Central Tertiary Basin. However, Marshall et al (2015) suggested a hyperthermal gradient of approximately 50°C/km which would result in uplift of about 2.5 km.…”
Section: Bolterdalen Bolterdalen Bolterdalen Bolterdalen Bolterdalen mentioning
confidence: 99%
“…Throndsen (1982) estimated uplift of about 3.5 km in western central Spitsbergen. Marshall et al (2015) suggested that the base-Paleocene has experienced maximum burial temperatures of 120 °C in the central part of the Central Tertiary Basin. However, Marshall et al (2015) suggested a hyperthermal gradient of approximately 50°C/km which would result in uplift of about 2.5 km.…”
Section: Bolterdalen Bolterdalen Bolterdalen Bolterdalen Bolterdalen mentioning
confidence: 99%
“…According to Levine (1993) the methane generated at lignite rank is not retained in coal due to absence of structure to retain economic quantity of gas at this stage and is expelled due to compaction. Contributions have also been made by Wilkins andGeorge (2002), Farhaduzzaman et al (2012), Gentzis (2013), Hakimi et al (2013) and Marshall et al (2015).…”
Section: Introductionmentioning
confidence: 88%
“…A recent study by Marshall et al . () suggests that the base Palaeocene has experienced maximum burial temperatures of 120°C in the central part of the Central Tertiary Basin with a hyperthermal gradient of approximately 50°C/km. Log data from Braathen et al .…”
Section: Geological Settingmentioning
confidence: 97%
“…Based on the results of Marshall et al . (), the Tempelfjorden Group in central Spitsbergen (study area) may have been subjected to temperatures up to 180 to 190°C around the Oligocene/Miocene boundary.…”
Section: Geological Settingmentioning
confidence: 99%